The Role of Culturists in Guiding the Local Wisdom Tradition of Pantang Kemali in Adolescents - Mawaddah Mawaddah; Misrah Misrah (Fakultas Tarbiyah Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aims to describe the role of cultural observers in guiding the Abstinence Kemali local wisdom tradition for adolescents in Kutacane, Southeast Aceh. The research subject MAA (Aceh Traditional Council) and "Kalak Metue Kute", as humanists who know the culture of the environment. This research is qualitative research with an ethnographic approach. They were conducted in Kutacane, Southeast Aceh, with the object of research looking at the role of cultural figures in guiding the local wisdom traditions of Pantang Kemali for adolescents. The research data is in the form of the role of cultural observers in guiding local wisdom traditions. The data source was obtained from the local wisdom Pantang Kemali. Data collection techniques were carried out through observation and interviews. At the same time, the data analysis was carried out by reducing the data on the role of cultural figures as a whole, presenting data on the role of cultural figures in guiding local wisdom traditions, and drawing conclusions. The study's findings demonstrate that humanists play a role in steering indigenous wisdom traditions Pantang Kemali in Kutacane through outreach, cultural custom training, and direct reprimands for children who disobey such traditions Pantang Kemali. It is necessary to expand techniques in preserving culture by taking advantage of the progress of the globalization era, such as showing existing culture on social media to continue prioritizing national culture for young people in the new era of society 5.0.